Riding the School Bus: A Comparison of the Rural and Suburban Experience in Five States - Aimee A. Howley; Steven Shamblen (Journal of Research in Rural Education, 2001)
This study examined the nature and experience ofriding the school bus in rural as compared to suburban locales in five states (Arkansas, Georgia, New Mexico, Pennsylvania, and Washington). Information about the nature and experience ofthe bus ride was provided by J,J94 elementary school principals who completed a survey instrument devised by the researchers. Results show differences that distinguish the school busing experience in rural and suburban locales by state. Among the most persistentfindings from state to state are the following: Elementary schools in rural locales are (a) more likely than suburban schools to have longest rides of30 minutes or more, (b) more likely to have attendance areas greater than J0 square miles, (c) more likely to have bus routes with rougher rides, (d) less likely to be located in districts that employ a full-time bus supervisor; and (e) more likely to include middle-school and/or high school students on the same bus runs as elementary students. This study provides empirical confirmation of the comparatively adverse conditions that contribute to the concerns expressed by rural parents and communities about the length and potential dangers ofrides experienced by students who attend rural elementary schools.